Increase of Optical Transfer Medium Transport Capacity and Consequent Increase of Safety and Reliability of Traffic - Godec, Andrej; Hernavs, Boštjan (Promet - Traffic&Transportation)
Over the past few years we have been witnessing a rapid andundreamt of development in the communications field. Every·one wants to communicate with others all the time. Industry isa major generator of these changes. But users do not like fastand frequent changes because they usually mean nothing good.The majority is satisfied with basic necessities and there is ahuge problem in t1ying to convince them into something new.There is a difference between technical and marketing sector.We are dealing with economy, promises, contracts. But industrywants more: new users, fresh money for new investments.The aim of this article is to find a technical solution for increasingthe existent optical cable capacities. The purpose is notto replace the existing cables but to use advanced technologyand to improve economy, safety and reliability of all kinds ofcommunications which use optical transmission medium.